Spectroscopic and Structural Studies on the Complex of Benzoic Acid Azo PhenylCalix[4]arene (BAPC) with Ce4+ - Thi Ngoc Le, Nguyen; Van Tan, Le (Asian Journal of Chemistry, 2012)
In the previous work, a reaction of Ce(IV) with (benzoic acid)(azo)phenylcalixarene (BAPC) at pH 6-7 has been studied. (Benzoic acid)(azo)phenylcalixarene reacted with Ce(IV) to form a 1:1 complex with maximum absorption at 515 nm and molar absorptivity of 7.81 × 104 L mol-1 cm-1. Beer's law was obeyed in the range of 5.0 × 10-6-2.0 × 10-5 mol L-1 of Ce(IV) and the detection limit was found to be 2.5 × 10-6 mol L-1. Based on complex formation, a new method has been built to determine cerium in soil samples. The sand samples are decomposed by mixed acid (conc. H2SO4 and HF) in platinum crucible, after cooling, the residue was dissolved in dilute HCl and cerium is separated together with the lanthanides in the form of oxalate from zirconium, iron and the phosphate ion. The oxalate precipitate is dissolved in concentration nitric acid. In this work, the FT-IR, MS, UV-VIS spectroscopy were used to provide the existence of complex and the molecule mechanics was also studied for structural optimization and calculating the energy of system, bonding lengths, bonding angles. Combining all data, the mechanism of the complex formation between BAPC and Ce4+ could be explained.